The influence of workload and compensation on employee performance at PT PLN (Persero) Unit Induk Pembangkitan Sumatera Bagian Selatan - Sari, Ira Maya; Perizade, Badia; Zunaidah, Zunaidah; Hadjri, Ichsan (International research journal of management, IT and social sciences, 2023)
This study investigates and analyzes the influence of Workload and Compensation on employee performance at PT PLN (Persero) Unit Induk Pembangkitan Sumatera Bagian Selatan (PLN UIKSBS). The research utilized primary data collected through questionnaires distributed to all 114 employees of PLN UIKSBS. The questionnaire served as the instrument to measure the variables under study. The collected data were then processed using statistical tools with multiple linear regression analysis. The research findings indicate a positive and significant relationship between Workload and employee performance at PLN UIKSBS and Compensation’s vivacious and significant compensation employee performance. Recommendations for PLN UIKSBS include improving and enhancing employee performance by considering Workload, such as re-evaluating employee placements based on educational backgrounds, especially in high-risk job areas. Additionally, attention should be given to employee compensation by disseminating rules and policies regarding the company’s incentive calculations and increasing efforts to provide opportunities for self-development through fair promotions to higher positions aligned with employee competencies and organizational needs.